2019
DOI: 10.3390/catal9040304
|View full text |Cite
|
Sign up to set email alerts
|

New Functionalized Polycycles Obtained by Photocatalytic Oxygenation Using Mn(III) Porphyrins in Basic Media

Abstract: According to our earlier observations, the products of photocatalytic oxygenations of furan and thiophene derivatives of benzobicyclo[3.2.1]octadiene with anionic and cationic manganese(III) porphyrin at pH = 7 strongly depended on the type and position of the heteroatom in the aromatic ring, as well as the charge of the photocatalyst. Hence, a significant pH increase (to 10) in these systems offered a reasonable tool to affect the diversity and yields of the oxygenation products. They were quantitatively sepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 22 publications
1
4
0
1
Order By: Relevance
“…Moreover, only one product kept the aromatic furan ring (as a hydroxylated one, 6), the transformation ceased the aromaticity of this heterocycle in the other cases. These results confirm that the aromatic character of furan is much weaker than that of thiophene, in accordance with our earlier observations in similar systems [16,18].…”
Section: Synthesis and Identification Of Photooxygenation Productssupporting
confidence: 93%
See 2 more Smart Citations
“…Moreover, only one product kept the aromatic furan ring (as a hydroxylated one, 6), the transformation ceased the aromaticity of this heterocycle in the other cases. These results confirm that the aromatic character of furan is much weaker than that of thiophene, in accordance with our earlier observations in similar systems [16,18].…”
Section: Synthesis and Identification Of Photooxygenation Productssupporting
confidence: 93%
“…Concerning the results obtained for the furyl derivative 1, all the photoproducts, 3-8 (Scheme 1), were isolated by repeated column and thin-layer chromatography and characterized by spectroscopic methods. From the 1 H NMR spectra and UPLC/MS analyses, taking our previous results [14,17,18] as reference, the structures of all the new compounds were determined. Molecular ions m/z 216 (3-5, 7, 8) and m/z 198 (6) indicated that one or two oxygen atoms were incorporated in the starting substrate 1, having masses 32 or 14 higher than the mass for 1 with m/z 184 (Scheme 1).…”
Section: Synthesis and Identification Of Photooxygenation Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…As previously emphasized, the prepared products 3-7 and 12, due to the presence of a double bond in their structure, could serve as potential starting precursors for further functionalization. These functionalizations, beside the addition reaction, could involve photooxygenation reactions (Scheme 5) [1,[22][23][24][25], previously studied in our laboratory. These reactions could result in a completely new spectrum of products, with preserved bicyclo[3.2.1.…”
Section: Resultsmentioning
confidence: 99%
“…The bicyclo [3.2.1]octane skeleton has become the subject of intensive research in recent years [1][2][3]. Its presence in numerous biologically active natural compounds ( Figure 1) [4][5][6][7], their strenuous isolation procedures from plants, as well as their complicated multistage synthesis due to the complexity of their structure, encouraged us to develop a simple one-step synthetic procedure based on a photochemical methodology [8][9][10][11][12][13][14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%